Numerical analysis of horizontally loaded piles reinforced with soil-cement blocks inserted on top (Research, Society and Development, 2022)
To better understand the influence of soil reinforcements in improved soil. A numerical study was performed on the influence of insertion of soil-cement blocks as reinforcement on the top of horizontally loaded piles, using 3D finite element models, evaluating the effect of different dimensions of reinforcements on the local soil. The simulated models were calibrated from the results of static load tests carried out on bored reinforced concrete piles, with and without the reinforcement of soil-cement block on the surface. Numerical models were built using Simulia™ Abaqus® v.6.13 software. The constitutive behavior of concrete and soil-cement was considered as Concrete Damaged Plasticity (CDP) and the soil was considered with Mohr-Coulomb’s constitutive model. Different dimensions of the reinforcement in relation to the diameter of the pile were then computationally simulated, identifying their influence on the load-displacement curve. As a result, the soil-cement block reinforcement improves the performance of the pile, reducing by up to 79.8% the horizontal displacements identified with the larges reinforcement analyzed.